ECONOMIC INDEPENDENCE OF PESANTREN: - Nasrullah, M.; Ismanto, Kuat; Nalim, Nalim (Hunafa: Jurnal Studia Islamika, 2018)
Islamic boarding school or pesantren is often only considered as a conservative Islamic educational institution. In fact, Pesantren has the number of interesting aspects to be deeply apart from studying the religion. As an institution, it involves many parties. The study aims to describe the economic map of Pesantren in Pekalongan region. This research is categorized as a field research using survey. The primary data were collected through questionnaires, interviews, and observations of the 25 Pesantren in Pekalongan region. The validation of data is done through triangulation of data and sources. Pesantren which became the object of this research are Pesantren which had established for at least three years and had a business unit. Based on the description of the research's findings and discussion, it was concluded that almost all Pesantren in Pekalongan region have a business unit. The existing business unit, mostly engaged in trade. The businesses itself is oriented to meet the internal needs of religious school, especially students. Pesantren has the role in determining every type of business unit and corporate governance run by the religious schools. The governance/management of the business unit was run in a simple, not follow the rules of modern business management yet. However, Pesantren have involved students in business management. The operations results of this business unit at least have contributed in boarding operations.